Desert Islands of Modernization. Social and Economic Contexts of Loneliness of the Figures in Polish Literature from the Second Half of the 19th Century - Tomczok, Paweł Tomczok (Porównania, 2019)
The article presents an analysis of the figure of Robinson in Adolf Dygasiński’s didactic novel Adventures of a young man, or Polish Robinson. Using the methodology of economics of literature, the ideologem of the work was examined, as well as the location of Dygasiński’s work in the context of peripheral capitalism. The transfer of the economic and literary figure from the context of English capitalism to Poland required many changes that allow to recognise the problematic status of the economic periphery of global capitalism.